2021
DOI: 10.1108/ecam-03-2021-0245
|View full text |Cite
|
Sign up to set email alerts
|

Effects of load carrying techniques on gait parameters, dynamic balance, and physiological parameters during a manual material handling task

Abstract: PurposeSince construction workers often need to carry various types of loads in their daily routine, they are at risk of sustaining musculoskeletal injuries. Additionally, carrying a load during walking may disturb their walking balance and lead to fall injuries among construction workers. Different load carrying techniques may also cause different extents of physical exertion. Therefore, the purpose of this paper is to examine the effects of different load-carrying techniques on gait parameters, dynamic balan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 95 publications
0
5
0
Order By: Relevance
“…In particular, 71% of the laboratory studies enrolled volunteers that did not have working experience related to the topic of the study and only 23% enrolled workers. In a minor number of laboratory studies (6%), the data were simulated starting from real recordings with biomechanical models (as in Brambilla et al [ 109 ]) or completely simulated. Conversely, 99% of the workplace papers had enrolled workers.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, 71% of the laboratory studies enrolled volunteers that did not have working experience related to the topic of the study and only 23% enrolled workers. In a minor number of laboratory studies (6%), the data were simulated starting from real recordings with biomechanical models (as in Brambilla et al [ 109 ]) or completely simulated. Conversely, 99% of the workplace papers had enrolled workers.…”
Section: Resultsmentioning
confidence: 99%
“…IMU sensors were used to analyze the total head movement and segment the gait, while an adaptive de-noising framework was built to describe and manage the motion artifact contamination in EEG readings. Using EDA and HR data, Anwer et al [57] investigated the impact of load bearing strategies on gait metrics, which indicated that carrying burdens with both hands increased gait symmetry, dynamic balance, and decreased the chance of falling.…”
Section: E Eeg and Imu Eda And Hrmentioning
confidence: 99%
“…Wearable biosensors with integrated EDA capabilities are used in construction safety studies to obtain physiological signals from workers to assess their stress levels and the physical demands required for different jobs ( Jebelli et al, 2019 ). For example, studies have found that workers with loads produce higher EDA values than those without loads ( Anwer et al, 2021 ), and EDA can also be used to predict concentration levels by monitoring workers’ biosignals ( Kim et al, 2021 ). EDA is often used in conjunction with VR in architectural design research to investigate the perception of human experience and emotional responses in architectural spaces and built environments ( Ergan et al, 2019 ).…”
Section: Knowledge Fusion Of Neuroscience Tools In Building Constructionmentioning
confidence: 99%